GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 5460 species occurrences available in GBIF matching the query: TaxonKey: Underwoodisaurus milii Bory, 1823. The dataset includes 5460 records from 40 constituent datasets: 21 records from AMNH Herpetology Collections. 1 records from Herp specimens. 22 records from UMMZ Herpetology Collection. 9 records from LACM Vertebrate Collection. 2160 records from Western Australian Museum provider for OZCAM. 15 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 7 records from KUBI Herpetology Collection. 2 records from Biodiversity Research and Teaching Collections - TCWC Vertebrates. 21 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 6 records from SMNS Herpetologie. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Herpetology. 1 records from Herpetology Collection - Royal Ontario Museum. 1 records from UCM Amphibian and Reptile Collection (Arctos). 1 records from Bernice P. Bishop Museum. 11 records from Fauna Atlas N.T.. 1 records from Ditsong Museum. 10 records from NMNH occurrence DwC-A. 475 records from Australian Museum provider for OZCAM. 21 records from Amphibians and Reptiles collection at the Natural History Museum of Denmark (SNM). 1 records from SDNHM Herpetology Collection. 1 records from Herpetology Collection. 1 records from NRM-Herpetology. 2 records from Lund Museum of Zoology (MZLU). 10 records from Natural History Museum (London) Collection Specimens. 1016 records from South Australian Museum Australia provider for OZCAM. 1 records from UMZC Zoological Specimens. 2 records from Herpetile collection, Natural History Museum, University of Oslo. 25 records from Australian National Wildlife Collection provider for OZCAM. 31 records from Museum of Comparative Zoology, Harvard University. 1 records from herpetology. 6 records from Collection Herpetologie - SNSD. 1 records from CM Herps Collection. 690 records from South Australia Fauna Observations. 587 records from OEH Atlas of NSW Wildlife. 18 records from CAS Herpetology (HERP). 2 records from Individual Sightings. 1 records from MVZ Herp Collection (Arctos). 262 records from Museum Victoria provider for OZCAM. 11 records from CUMV Reptile Collection (Arctos).
Keywords: GBIF; biodiversity; species occurrences